Genotype by environment interactions for damage caused by Diatraea spp. borers in sugarcane (2018)
Diatraea spp. (Lepidoptera: Crambidae) or sugarcane stem borers are important sugarcane pests in Venezuela. The use of resistant cultivars is part of an integrated management to control these insects in many countries. The aim of this study was to evaluate a group of sugarcane genotypes for Diatraea damage in several environments, and to assess the interaction among damage caused by Diatraea and yield components. Data were collected from five sugarcane field trials located in plots belonging to the Venezuelan Sugarcane Breeding Program. Twenty genotypes were evaluated for Diatraea damage in a completely randomized block design with three replicates. AMMI and GGE biplot analyses were executed for infestation intensity (II). Genotypes that showed best stability, good yield and low damage from Diatraea spp. across environments were V99-236, V00-50 and V99-190. Cultivar CP74-2005 was the most affected by injuries of sugarcane stem borers throughout locations. Intensity of infestation (II) and index of damage (ID) were highly associated. Furthermore, high intensity of infestation (II) and index of damage (ID) caused by Diatraea disturbed the Pol % cane of the genotypes.